2011
DOI: 10.1007/s12262-011-0237-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Pyeloplasty: Comparison of Two Surgical Approaches- A Single Centre Experience of Three Years

Abstract: UPJO causes hydronephrosis and progressive renal impairment may ensue if left uncorrected. Open pyeloplasty remains the standard against which new technique must be compared. We analyzed the comparison of Laparoscopic and open pyeloplasty in a randomized prospective trial. A prospective randomized study was done from January 2004 to January 2007 in which a total of 28 Laparoscopic and 34 open pyeloplasty were done. All laparoscopic pyeloplasties were performed transperitoneally. Standard open Anderson Hynes py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…However, mean hospital stay was shorter than that of the RP (p=0.047). In a study conducted by Bansal et al [20] lesser amount of postoperative analgesic requirement was reported in LP patients relative to open pyeloplasty (mean, 107.14 mg vs 682.35 mg, p<0,01). Besides in the same study, mean hospital stay was reported as 8.29 days in open pyeloplasty, and 3.14 days in the LP group (p<0.01).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…However, mean hospital stay was shorter than that of the RP (p=0.047). In a study conducted by Bansal et al [20] lesser amount of postoperative analgesic requirement was reported in LP patients relative to open pyeloplasty (mean, 107.14 mg vs 682.35 mg, p<0,01). Besides in the same study, mean hospital stay was reported as 8.29 days in open pyeloplasty, and 3.14 days in the LP group (p<0.01).…”
mentioning
confidence: 88%
“…In a study conducted by Bansal et al [20] in 2011, the investigators determined mean operative times in patients who had undergone LP, and open pyeloplasty as 244, and 122 minutes, respectively (p<0.01). In this study where Bansal et al compared LP with open method, and emphasized longer operative time of LP as the only disadvantage of this approach.…”
mentioning
confidence: 99%
“…2 Endopyelotomy is a third option that is less invasive than both the open and minimally invasive pyeloplasties. 3 While all these treatments are effective, [3][4][5][6] the extent to which they are used is unclear. Although recent studies have shown a rapid increase in the use of minimally invasive pyeloplasty, many of them only compare inpatient procedures (i.e., open and minimally invasive pyeloplasty) and exclude outpatient treatments (i.e., endopyelotomy).…”
Section: Introductionmentioning
confidence: 99%
“…inimally invasive pyeloplasty is an effective treatment for patients with ureteropelvic junction obstruction that offers quicker convalescence, 1 decreased postoperative pain, 1,2 and improved cosmesis 3 compared with the conventional open pyeloplasty. With success rates greater than 90%, minimally invasive pyeloplasty has equivalent outcomes to those of open pyeloplasty 4 and superior outcomes to those of endopyelotomy.…”
mentioning
confidence: 99%